Epithelial cell dysfunction, a major driver of asthma development. Issue 8 (16th June 2020) - Heijink, Irene H.; Kuchibhotla, Virinchi N. S.; Roffel, Mirjam P.; Maes, Tania; Knight, Darryl A.; Sayers, Ian; Nawijn, Martijn C.
Abstract: Airway epithelial barrier dysfunction is frequently observed in asthma and may have important implications. The physical barrier function of the airway epithelium is tightly interwoven with its immunomodulatory actions, while abnormal epithelial repair responses may contribute to remodelling of the airway wall. We propose that abnormalities in the airway epithelial barrier play a crucial role in the sensitization to allergens and pathogenesis of asthma. Many of the identified susceptibility genes for asthma are expressed in the airway epithelium, supporting the notion that events at the airway epithelial surface are critical for the development of the disease. However, the exact mechanisms by which the expression of epithelial susceptibility genes translates into a functionally altered response to environmental risk factors of asthma are still unknown. Interactions between genetic factors and epigenetic regulatory mechanisms may be crucial for asthma susceptibility. Understanding these mechanisms may lead to identification of novel targets for asthma intervention by targeting the airway epithelium. Moreover, exciting new insights have come from recent studies using single‐cell RNA sequencing (scRNA‐Seq) to study the airway epithelium in asthma. This review focuses on the role of airway epithelial barrier function in the susceptibility to develop asthma and novel insights in the modulation of epithelial cell dysfunction in asthma.